Entrepreneurship characteristics, business location and entrepreneurship competency towards business success of garage - Angga Gultom (Marketing Management Studies, 2021)
The aim of this study was to examine the influence of entrepreneurial characteristics, business premises and entrepreneurial competence on the success of the motorbike workshops business in Baturaja. This study is a quantitative study using the ex post facto method. The population in this study were 978 automotive businesses in East Baturaja, while the sample in this study used a purposive sample where 30 samples were obtained, all of which were motorbike workshops. The results of this study indicated that the entrepreneurial characteristics variable dif not have a significant effect on the success of the business as evidenced by the t-count (0.-216) <t-Tabel (2.056), while other variables had a significant effect on the success of the business in the workshop business in East Baturaja District. It was shown that the t-count value of business location (4.178)> t-Tabel 2.056 and t-count of competency abilities (6,022)> t-Tabel 2.056.